2008
DOI: 10.1007/s10384-007-0485-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of real-time polymerase chain reaction for diagnosis of herpetic diseases of the anterior segment of the eye

Abstract: Real-time PCR is an informative method of diagnosing herpetic eye diseases and evaluating the possible involvement of HSV in other inflammatory ocular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 19 publications
2
23
0
2
Order By: Relevance
“…In all the cases described in our study, a real-time PCR assay was used. The use of PCR for the diagnosis of HSV is claimed to be equally specific and possibly more sensitive than the cell cultures (Kakimaru-Hasegawa et al 2008;Espy et al 2000). PCR-based techniques have been successfully employed on various clinical samples including tear film, corneal epithelium and corneal buttons.…”
Section: Discussionmentioning
confidence: 99%
“…In all the cases described in our study, a real-time PCR assay was used. The use of PCR for the diagnosis of HSV is claimed to be equally specific and possibly more sensitive than the cell cultures (Kakimaru-Hasegawa et al 2008;Espy et al 2000). PCR-based techniques have been successfully employed on various clinical samples including tear film, corneal epithelium and corneal buttons.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with infections of herpes simplex virus or varicella zoster virus as determined by real-time PCR of the aqueous humor samples were excluded [4]. In addition, systemic examinations were performed to determine if systemic inflammatory disorders, infectious diseases, or neoplastic diseases were the cause of the diseases.…”
Section: Patientsmentioning
confidence: 99%
“…The aqueous humor was collected by paracentesis, and DNA was extracted from the aqueous humor with the QIAamp DNA mini kit (Qiagen, Hilden, Germany) [4]. The glycoprotein B gene of CMV was amplified with the LightCycler (Roche, Basel, Switzerland) as described [15].…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…4A) and found that a significantly lower level of VEGF was secreted from the infected HCECs. To determine whether the reduced VEGF level was due to a blockage of virus replication, we used real-time PCR 19 and a plaque assay to quantify the HSV-1 genome. Replication of the HSV-1 genome was not significantly affected by IL-6 blockade (cells control treated at MOI 0.1 yielded 9.2 Ϯ 0.9 ϫ 10 3 copies/L and anti-IL-6-treated at MOI 0.1 yielded 1.0 Ϯ 0.2 ϫ 10 4 copies/L, P Ͼ 0.05).…”
Section: Inductive Effect Of Il-6 On Vegf In Hsv-infected Hcecsmentioning
confidence: 99%